Strength and conditioning of adolescent male cricket players - Pote, Lee (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
Background: Modern day cricketers are faced with longer, more strenuous seasons which are more physically demanding than the traditional forms of the game. Due to these increased physical demands, players are more prone to both overuse injuries, particularly of the lower back (bowlers) and lower limbs (batsmen), as well as acute, impact injuries (fielders/wicket keepers). The increase in injury risk is of particular concern at younger levels as research has shown that adolescents are at a higher risk for injury than their adult counterparts. Therefore, there is a need for strength and conditioning programs that reduce the risk of injury and improve performance at this level. However, of the programs that are available, most are not multi-factorial in nature and are aimed at elite cricketers. This is of concern in low-to-middle income countries such as South Africa, where players often do not have access to facilities or equipment and thus need to be exposed to low-cost, no-cost training programs. Furthermore, most information is anecdotal and there is a distinct lack of injury prevention programs at an adolescent level. Objective: The purpose of this thesis was to investigate the strength and conditioning practices of adolescent cricket players, particularly from a South African context, where there is a distinct lack of resources. This was through the completion of three phases; firstly, a literature review was completed to determine the information currently available on injury prevention strategies in cricket. The review also examined the injury statistics of five major playing cricket nations. Secondly, a survey was conducted to determine the current strength and conditioning practices of schoolboy and university coaches in South Africa. Lastly, a novel intervention program (CricFit) was designed and implemented within an adolescent population. The main purpose of the intervention was to determine whether players' physical fitness parameters improved over time and whether the risk of injury was reduced. Methods: For phase one of the
Keywords: Cricket -- South Africa; Cricket injuries -- South Africa; Cricket Physiological aspects; Cricket Coaching -- South Africa; Physical fitness for youth -- South Africa; CricFit